EFEKTIVITAS PEMBERIAN ASTAXANTHIN PADA Daphnia sp. DENGAN DOSIS BERBEDA TERHADAP KECERAHAN WARNA DAN PERTUMBUHAN BENIH IKAN MAS KOKI (Carassius sp) - Sarma Octaviani Nainggolan; Siti Komariyah; Andika Putriningtias (Bajang Institute, 2024)
Goldfish (Carrassius sp.) is a type of ornamental fish with interesting color variations. Color is one of the reasons ornamental fish are in demand by the public, so farmers need to improve the quality of color in ornamental fish. To increase the brightness of color in goldfish fry, it is necessary to add carotenoids to the feed. The aim of this research was to determine the best dose of astaxanthin to increase color brightness in goldfish (Carassius sp.) fry. The method used in this research was RAL with 4 treatments and 3 repetitions, namely P1 (0.00 g/30 ml), P2 (0.20 g/30 ml), P3 (0.30 g/30 ml), P4 ( 0.50 g/30 ml). The parameters observed during the research were the brightness of the fish's color, absolute length growth, absolute weight growth, survival rate and water quality. The results showed that giving astaxanthin to Daphnia sp. had a significant effect on increasing color brightness, but did not have a significant effect on growth in length, weight and survival rate of goldfish (Carassius sp.) fry